Nighttime light intensity and brightness suitability in urban functional zones - Ming Liu; Ruicong Li; Yiwei Li; Ezzaddeen Ali Mohammed Saeed AL-Mowallad; Chenglong Wu; Wenjing Wang (Scientific Reports)
Abstract The identification and distribution of urban functional zones play a crucial role in optimizing urban planning and resource allocation. The differences in brightness of the nocturnal light environment further reveal the characteristics of urban functions. This study takes the main urban area of Dalian as an example, integrates Point of Interest and OpenStreetMap data to generate functional zone samples, and proposes a multi-scale evaluation framework at the levels of administrative districts, streets, and blocks, combined with Luojia-1 night-time remote sensing imagery. The results show that: (1) Significant differences in brightness exist among functional zones within the study area, and there is a mismatch between actual demand and nighttime light brightness; (2) The Average Nighttime Radiance per Unit Area and Brightness Factor can more accurately reflect the distribution characteristics of urban nighttime light brightness; (3) Clustering based on the Brightness Factor reveals over-bright and under-bright blocks, identifying commercial and port-industry areas as hotspots of excessive nighttime lighting. This study dissects the spatial heterogeneity of the nocturnal light environment from the perspective of urban functional zoning and provides quantitative support for the development of differentiated lighting management policies.